Emissions of pollutant gases, fine particulate matters and their significant tracers from biomass burning in an open-system combustion chamber - Somporn Chantara (2019)
© 2019 An open-system combustion chamber was designed and constructed for simulation of burning of various biomass types to estimate emission factors of pollutant gases, fine particulate matters and their composition to find out significant tracers. Rice straw (RS), maize residues (MR) and forest leaf litters (FLL) from mixed deciduous forest (MDF) and dry dipterocarp forest (DDF) were collected from various places in Northern Thailand based on land-use types. Approximately 1 kg of air-dried biomass sample was burned in the chamber, PM 2.5 were collected. CO 2 dominated during the flaming state while CO is predominant in the smoldering state. The highest EF PM2.5 was obtained from MDF burning (4.38 ± 2.99 g kg −1 ), while the lowest value was from MR burning (2.15 ± 0.95 g kg −1 ). Among water soluble ions, K + (biomass burning (BB) tracer) was the most abundant species in PM 2.5 followed by Cl − and SO 42− . The average EF K+ from the burning of agricultural biomass was significantly higher than the burning of FLL. Scatter plot of K + /SO 42− versus K + /Cl − can be used to distinguish between agricultural crop residues and FLL burning. Levoglucosan (BB tracer) was a dominant species among anhydrosugars and also a major component found in FLL burning. The ratios of levoglucosan/K + and levoglucosan/mannosan obtained from forest and agricultural waste burnings were significantly different, therefore they can be used for BB source identification.